Public space and citizen participation: an extensionist experience in the city of Neuquén (Argentina) (Huellas, 2022)
The article addresses the analytical and factual derivations of a university extension project on public space, which articulated a process of participation of different social organizations, institutions, and the community of the Cuenca XV neighborhood of the city of Neuquén. From the methodological point of view, the participatory action research approach was applied as a way of transferring knowledge and reciprocal experiences, thus promoting self-learning, both for the extension team and the neighborhood community. The institutionalized confinement to prevent the spread of SARS-CoV2 forced us to take into account new alternatives for obtaining data and rethinking the methodologies of citizen participation, through the articulation of virtual meetings and workshops. The project generated new demands and perspectives, promoted by the territorial actors themselves in the framework of a collective reflection that allowed the revaluation of public space.
Keywords: public space; urban space; social participation; citizen education; Cuenca XV neighborhood